Clay minerals of surface sediments from the lower Bengal Fan: Implications for provenance identification and transport processes. (16th February 2020) - Sun, Xingquan; Liu, Shengfa; Fang, Xisheng; Li, Jingrui; Cao, Peng; Zhao, Guangtao; Khokiattiwong, Somkiat; Kornkanitnan, Narumol; Shi, Xuefa
Abstract : Based on the clay mineral assemblages of 98 surface sediments from the lower Bengal Fan, we carried out a quantitative provenance identification and discussed the potential transport processes of fine fractions with the support of the hydrodynamic environment. Illite is the dominant clay mineral in the study area, with an average of 51%, followed by kaolinite, with an average of 20%, while chlorite and smectite account for averages of 17 and 11%, respectively. The study area can be divided into two provinces based on the clay mineral assemblages: Province I, located in the western part of the study area, has relatively higher smectite content, while province II, located in the eastern part, shows higher illite content. The Ganges–Brahmaputra (Himalayan) and the Godavari–Krishna (Indian Peninsula) are suggested to be the major provenances, and the average relative contributions of the Himalayan source and the Indian source are 76 and 24%, respectively. Sediments in province II receive more sediment from the Himalayan source, with an average contribution of 84%, while the Indian source mainly contributed to province I, with an average contribution rate of 32%. The Indian Peninsula materials are predominantly conveyed to the study area by the northeast monsoon circulation, and the relative contribution gradually decreases from northwest to southeast in the lower Bengal Fan. However, most of the Himalayan material is transported to the study area by the southwest monsoon. Our research indicates that the seasonal hydrodynamic pattern of the Northeast Indian Ocean plays an important role in controlling modern sediment transport in the Bay of Bengal, causing terrestrial materials from different sources to show significantly different spatial distribution characteristics.